Dynamics of Listeria monocytogenes colonisation in a newly-opened meat processing facility. (March 2016) - Bolocan, Andrei Sorin; Nicolau, Anca Ioana; Alvarez-Ordóñez, Avelino; Borda, Daniela; Oniciuc, Elena Alexandra; Stessl, Beatrix; Gurgu, Leontina; Wagner, Martin; Jordan, Kieran
Abstract: This study determined the colonisation scenario of Listeria monocytogenes in a newly-opened ready-to-eat meat processing facility using a combination of classical microbiology and molecular biology techniques. Samples (n = 183), including food contact surfaces, non-food contact surfaces, raw materials and food samples, collected on four sampling occasions, were analysed for L. monocytogenes by the ISO 11290:1996 standard method and by real-time PCR applied to the second enrichment broth from the ISO method. No L. monocytogenes were detected on the first sampling occasion, but by the second sampling occasion a persistent clone had colonised the facility. Analysis of the second enrichment of the ISO method by real-time PCR was more sensitive for the detection of L. monocytogenes than the ISO method alone. In order to reduce the risk of cross contamination and the public health risk, awareness and proactive measures are required to control L. monocytogenes from the first days of production in a newly opened meat processing facility. Highlights: Colonization dynamics of a newly-opened meat processing facility by Listeria monocytogenes is presented. Colonisation scenarios were created using a combination of classical microbiology and molecular biology methods. The prevalence established by ISO 11290 combined with RTi-PCR has higher values than that obtained by ISO 11290 alone. The results make processors aware on how fast L. monocytogenes installs in a meat processing facility and how important is to prevent cross contamination.